Night bird calling - Gohlke, Cathy (Tyndale House Publishers, 2020)
"When Lilliana Swope's beloved mother dies, Lilliana gathers her last ounce of courage and flees her abusive husband for the home of her only living relative in the foothills of No Creek, North Carolina. Though Hyacinth Belvidere hasn't seen Lilliana since she was five, she offers her cherished great-niece a safe harbor. Their joyful reunion inspires plans to revive Aunt Hyacinth's estate and open a public library where everyone is welcome, no matter the color of their skin. Slowly Lilliana finds revival and friendship in No Creek - with precocious eleven-year-old Celia Percy, with kindhearted Reverend Jesse Willard, and with Ruby Lynne Wishon, a young woman whose secrets could destroy both them and the town. When the plans for the library also incite the wrath of the Klan, the dangers of Lilliana's past and present threaten to topple her before she's learned to stand. With war brewing for the nation and for her newfound community, Lilliana must overcome a hard truth voiced by her young friend Celia: Wishing comes easy. Change don't."--Provided by publisher.